Immune-Mediated Thrombocytopenia in adults: Treatment Updates - Khan, Md Rafiquzzaman (Bangladesh Journal of Medicine, 2023)
Immune Thrombocytopenia (ITP) is an acquired low platelet count resulting from immune-mediated platelet destruction and/ or impaired platelet production. Primary ITP is idiopathic and secondary ITP is associated with another conditions. The incidence is 1 to 6 per 100,000 adults. ITPmay present without symptom or present with bleeding. Bleeding manifestations are minor (skin/mucous membrane), critical (e.g. intracranial, intraocular, retroperitoneal, intramuscular bleeding etc) and severe (fall in hemoglobin of 2 g/dL or requires transfusion of e”2 units of red cells).ITP is diagnosed on the basis of isolated thrombocytopenia without anemia or leukopenia. There are no reliable laboratory tests to confirm the diagnosis. The aim of treatment of ITP is to provide a safe platelet count to prevent bleeding, rather than to normalize the platelet count. Treatment options of ITP are the Firstline therapies, second-line therapies and therapies. First-line therapy are for patients with severe bleeding and platelet count <30x10^9/L, which includes platelet transfusion, glucocorticoids (e.g. methylprednisolone, 1 g IV, daily for 3 doses; or dexamethasone, 40 mg orally or IV, daily for four days), IVIG and IV globulin. Second-line therapy is indicated for patients with thrombocytopenia associated with significant bleeding or for severe, persistent or recurrent thrombocytopenia (e.g., platelet count <20x10^9/L) following glucocorticoid-based treatments. Secondline therapies include splenectomy, rituximab, thrombopoietin receptor agonist or immunosuppressive therapy. Other therapies include danazol, vincristine, procarbazine, etoposide etc, or combination therapy. Indications of treatment are (1).Severe bleeding and platelet count <30x10^9/L. (2). Newly diagnosed ITP and any clinically important bleeding (3) Newly diagnosed ITP and platelet count <20x10^9/L, even in absence of bleeding (4) Patients with platelet counts >30x10^9/L having risk of bleeding, other hemostatic defects or require surgery.Spontaneous remission occurs in up to 10% of adults with ITP. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 189-190